Platelet-rich plasma relieves inflammation and pain by regulating M1/M2 macrophage polarization in knee osteoarthritis rats - Jiawei Xu; Xiuping Chen; Haina Zhang; Xiyue Zhang; Rujuan Liu; Xin Li; Junwei Wang; Tieshan Li (Scientific Reports)
Abstract Knee osteoarthritis (KOA) is a common, chronic, degenerative disease. Platelet-rich plasma (PRP) can significantly relieve KOA pain; however, the mechanism of PRP-induced analgesia remains to be studied. Macrophages are closely related to KOA pain, and regulating macrophage polarization may be an effective way to relieve KOA pain. Therefore, the aim of this study is: First, to explore whether PRP can effectively relieve pain in a KOA animal model and whether it relieves pain by regulating macrophage polarization. Second, to explore the mechanism by which PRP regulates macrophage polarization. Thirty-six healthy male SD rats were randomly divided into sham group, MIA group and PRP group. The KOA rat model was established by injecting 1 mg of MIA into the joint cavity. Behavioral tests, including weight-bearing asymmetry, hot plate, and von Frey hairs tests, were performed. The positive expression rates of inducible nitric oxide synthase (iNOS) and CD163 in the synovium were detected via immunohistochemical staining. Meanwhile, RAW 264.7 cells induced by lipopolysaccharide were treated with PRP in vitro. The production levels of the nuclear factor kappa-B (NF-κB) pathway-related proteins NF-κB p65, inhibitor-κ binding protein α (IκBα), p-NF-κB p65, p-IκBα and the iNOS and CD163 proteins were measured via western blotting. An enzyme-linked immunosorbent assay was used to detect the release of tumor necrosis factor-α (TNF-α), interleukin-1 beta (IL-1β), interleukin-10 (IL-10), and nerve growth factor (NGF). The behavioral results revealed that PRP relieved pain. PRP reduced the proportion of M1/M2 macrophages among synovial macrophages, significantly inhibited the secretion of TNF-α and IL-1β in the synovium, and increased the secretion of IL-10. In addition, in vivo experiments revealed that PRP decreased the protein expression of iNOS, p-IκBα/IκBα, and p-p65/p65 and increased the protein expression of CD163. Furthermore, PRP decreased TNF-α, IL-1β, and NGF levels in RAW 264.7 cells and increased the secretion of IL-10. Our findings indicate that PRP can improve long-term relief from KOA pain. The analgesic mechanism promotes the transformation of M1 macrophages to M2 macrophages by inhibiting the NF-κB signaling pathway, which reduces the release of downstream pain-causing factors, thus relieving inflammation and pain.